Concise synthesis of (-)-deoxoprosopinine - Pandey, Satyendra Kumar; Kumar, Pradeep (Synlett, 2007)
A simple and highly efficient approach to (-)-deoxoprosopinine from racemic epoxide as a starting material is described employing a Jacobsen's hydrolytic kinetic resolution (HKR) and Sharpless asymmetric dihydroxylation (AD) as key steps.
Keywords: hydroboration-oxidation; Jacobsen's HKR; Piperidine alkaloids; sharpless AD; Total synthesis

Chiral Mn(III) salen complex immobilized onto ionic liquid modified mesoporous silica for oxidative kinetic resolution of secondary alcohols - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Tetrahedron Letters, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a chiral Mn(III) salen complex onto ionic liquid modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high enantioselectivity and activity in the oxidative kinetic resolution of secondary alcohols, and could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Mesoporous silica SBA-15; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Concise synthesis of protected (2S,4R)-4-hydroxyornithine - Pandey, Satyendra Kumar; Pandey, Menaka; Kumar, Pradeep (Tetrahedron Letters, 2008)
A short synthesis of the nonproteinogenic amino acid, (2S,4R)-4-hydroxyornithine is described. Starting from racemic benzyl glycidol, the scaffold of the target compound was constructed in high enantio- and diastereoselectivity using Jacobsen's hydrolytic kinetic resolution (HKR) and regioselective opening of an epoxide as key steps. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Epoxide; Grignard reaction; hydroxyornithine; Jacobsen's HKR; Natural product

Concise synthesis of (2S,3S,4S)-2-(Hydroxymethyl)pyrrolidine-3,4-diol (LAB1) - Upadhyay, Puspesh K.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
The synthesis of (2S,3S,4S)-2-(hydroxymethyl)pyrrolidine-3,4-diol (LAB1) from Garner's aldehyde is described using the Sharpless asymmetric dihydroxylation as the key step.
Keywords: alkaloid; azasugars; diastereoselectivity; Garner's aldehyde; pyrrolidine; Wittig reaction

Concise synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate - Ramalingam, S.; Bhise, Ankushkumar D.; Show, Krishanu; Kumar, Pradeep (Arkivoc, 2013)
An efficient synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate 1, a common intermediate for various polyhydroxylated piperidines is reported in six steps with 32% overall yield starting from Garner's aldehyde. The key steps include the diastereoselective nucleophilic addition and intramolecular cyclization. (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate is a common precursor for the synthesis of 1-deoxy-L-mannojirimycin, 1-deoxy-L-idonojirimycin, L-fagomycin and related analogues.
Keywords: cyclization; Garner's aldehyde; nucleophilic addition; polyhydroxy piperidines

Chemoselective deprotection of N-allylic amines using DDQ - Kumar, Pradeep; Cherian, Shijo K.; Jain, Ruchi; Show, Krishanu (Tetrahedron Letters, 2014)
A highly chemoselective and simple method for the deprotection of N-allylic amines using DDQ has been developed. The use of DDQ in dichloromethane-water provides a mild and efficient one-step deallylation of a wide variety of orthogonally protected tertiary amine derivatives. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Chemoselective deprotection; DDQ; N-Allylic amines; Orthogonally protected tertiary amines

Clay-supported copper nitrate (Claycop): a mild reagent for the selective nitration of aromatic olefins - Begari, Eeshwaraiah; Singh, Chandani; Nookaraju, U.; Kumar, Pradeep (Synlett, 2014)
A straightforward and highly selective method has been developed for the nitration of a wide variety of aromatic and aliphatic olefins by using a clay-supported copper nitrate (Claycop) and a catalytic amount of (2,2,6,6-tetramethylpiperidin-1-yl)oxyl, an inexpensive and mild reagent system. High conversions and exclusive E-selectivity, together with the environmentally benign nature of the Claycop reagent, make this a green method and an attractive alternative to established methods.
Keywords: alkenes; nitrations

Croncise organocatalytic route to protected (2S, 4R)-4-hydroxyornithine and(+)-pseudohygroline - Jha, Vishwajeet; Kumar, Pradeep (Synlett, 2014)
A practical, efficient, and organocatalytic approach to the synthesis of (2S,4R)-4-hydroxyornithine and (+)-pseudohygroline is reported using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and Horner-Wadsworth-Emmons olefination reaction of an aldehyde as the key step.
Keywords: aldehydes; Amination; Amino alcohols; cyclization; Enantioselectivity; Wittig reaction

Carbon-carbon bond forming reactions: application of covalently anchored 2,4,6-triallyloxy-1,3,5-triazine (TAT) Pd(II) complex over modified surface of SBA-15 to Heck, Suzuki, Sonogashira and Hiyama cross coupling reactions - Singh, Chandani; Jawade, Kiran; Sharma, Priti; Singh, Anand P.; Kumar, Pradeep (Catalysis Communications, 2015)
A highly active SBA-15-TAT-Pd(II) catalyst was synthesized from organofunctionalized SBA-15 and 2,4,6-triallyloxy-1,3,5-triazine. The catalyst was employed in carrying out Heck, ``copper-free'' Sonogashira, Suzuki and Hiyama cross coupling reactions. Under the optimized conditions the catalyst displays excellent catalytic activity in delivering the desired products in good to excellent yields. The catalytic system exhibited superior activity regarding the time taken for the completion of reaction, isolation, Pd loading (0.62 mmol%) and yields of products as compared to the earlier reported heterogeneous SBA-15 anchored Pd catalysts. The catalyst could be recycled and reused for five times without any appreciable loss of catalytic activity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heck; Hiyama; SBA-15-TAT-Pd(II) catalyst; Sonogashira; Suzuki

CeCl3 center dot 7H(2)O-NaI promoted regioselective sulfenylation of indoles with sulfonylhydrazides - Nookaraju, U.; Begari, Eeshwaraiah; Yetra, Ravikiran Reddy; Kumar, Pradeep (Chemistryselect, 2016)
A simple and highly efficient method has been developed for the regioselective sulfenylation of a wide variety of indoles with alkyl and aryl sulfonylhydrazides as a sulphur source and CeCl3 center dot 7H(2)O-Nal as an inexpensive and readily available reagent system. This method involves the breaking of sulfur-oxygen and sulfur-nitrogen bonds and making of carbon-sulfur bond. The method provides high yields of the products with enhanced regioselectivity. We studied the reactivity of various electron rich and electron deficient indoles towards the sulfe-nylation reaction. The indoles containing electron donating group reacts fast towards the sulfenylation reaction as compared to the indoles containing electron withdrawing groups. More over functional groups like alkoxy, aryloxy, bromo, nitro, cyano, ester, were well tolerated under the established reaction conditions. We also proposed a plausible mechanism for this transformation. The experimental simplicity and environmentally benign nature of the reagent system makes this method an attractive alternative to established methods.